siRNA-induced silencing of hypoxia-inducible factor 3α (HIF3α) increases endurance capacity in rats - S Drozdovska; B Gavenauskas; T Drevytska; V Nosar; V Nagibin; I Mankovska; V Dosenko (Termedia Publishing House, 2016)
Molecular mechanisms of adaptation to exercise despite a large number of studies remain unclear. One of the crucial factors in this process is hypoxia inducible factor (HIF) that regulates transcription of many target genes encoding proteins that are implicated in molecular adaptation to hypoxia. Experiments were conducted on 24 adult male Fisher rats. Real-time PCR analysis was performed for quantitative evaluation of Hif3α, Igf1, Glut-4 and Pdk-1 in m. gastrocnemius, m. soleus, in lung and heart tissues. Mitochondrial respiratory function and electron microscopy were performed. Knockdown of Hif3α using siRNA increases time of swimming to exhaustion by 1.5 times. Level of mitochondrial NAD- and FAD-dependent oxidative pathways is decreased, however efficiency of phosphorylation is increased after Hif3α siRNA treatment. Expression of HIF target genes in muscles was not changed significantly, except for increasing of Pdk-1 expression in m. soleus by 2.1 times. More prominent changes were estimated in lung and heart: Igf1 gene expression was increased by 32.5 and 37.5 times correspondingly. Glut4 gene expression in lungs was increased from undetected level till 0.3 rel. units and by 84.2 times in heart. Level of Pdk1 gene expression was increased by 249.2 in lungs and by 35.1 times in hearts, correspondingly. Some destructive changes in muscle tissue were detected in animals with siRNA-inducing silencing of Hif3α.